Service Quality Analysis Using Servqual and Importance Performance Analysis (IPA) Methods (Case Study of Sidomulya Village, Astanapura District) - Iksan Nendi; Iim Rohimatun Nahdiyyah; Tantra Agun Wiguna; Andika Bagus Saputra; Iin Tarsini (Journal of Social Research, 2025)
Public services at the village level play a crucial role in government implementation and significantly affect community satisfaction. However, gaps often exist between public expectations and their perceptions of service quality. This study aims to measure the quality of public services in Sidomulya Village, Astanajapura District, using the Service Quality (Servqual) method to identify the gap between expectations and perceptions, and to determine priority areas for improvement using Importance-Performance Analysis (IPA). Data were collected via questionnaires distributed to 30 respondents and analyzed through validity and reliability tests, followed by Servqual gap analysis and IPA quadrant mapping. The Servqual analysis revealed negative gaps across all dimensions of service quality—Tangibles (-0.39), Reliability (-0.97), Responsiveness (-0.53), Assurance (-0.40), and Empathy (-0.20)—with an average gap of -0.83, indicating that service quality does not meet public expectations. The largest gap was found in the Reliability dimension, highlighting concerns about service dependability. IPA results showed that aspects P1 and P9, related to administrative services and targeted social assistance, respectively, fall into the Top Priority quadrant, signaling urgent need for improvement. These findings suggest that the village government should prioritize enhancing these key service areas to better align with community expectations, thereby increasing public trust and satisfaction. This integrated application of Servqual and IPA provides a strategic framework for evaluating and improving village-level public services.